Antibacterial Pure Magnesium and Magnesium Alloys for Biomedical Materials—A Review - Qingfeng Song; Lingzhi Yang; Fang Yi; Chao Chen; Jing Guo; Zihua Qi; Yihan Song (Crystals)
Implant-related infections are one of the major challenges faced by orthopedic surgeries. Developing implants with inherent antibacterial properties is an effective strategy to address this issue. Biodegradable magnesium and magnesium alloys have become a research hotspot due to their good bioactivity, mechanical properties, biocompatibility, and excellent antibacterial ability. However, magnesium and its alloys have rapid corrosion, and the difficulty in expelling harmful magnesium ions and hydrogen gas produced by degradation from the body. This review summarizes the mainstream surface modification techniques such as laser surface modification, friction stir processing, and micro-arc oxidation, along with their impact on the antimicrobial properties of magnesium-based materials. This paper reviews the latest research progress on improving the antibacterial properties of magnesium alloys through alloying and introduces the antibacterial effects of mainstream magnesium alloys and also elaborates on the antibacterial mechanism of magnesium alloy materials. It is expected to provide more basis and insights for the design of biodegradable magnesium alloys with antibacterial properties, thereby promoting their development and clinical application.